A rare case of 5p-deletion in a child: Cri-du-chat syndrome - Narayanan, Rajeshwari; Arunachalam, Savitha; Jagannathan, Prahada (International Journal of Contemporary Pediatrics, 2022)
The Cri-du-chat syndrome (CdCS; OMIM#123450) is a contiguous gene syndrome caused by a variable deletion of the short arm of the chromosome 5 (5p-). The incidence ranges from 1:15,000 to 1:50,000 live-births. The CdCS diagnosis is suspected in a child with cat like cry during infancy, facial dysmorphisms, hypotonia and delayed psychomotor development. Genotype-phenotype correlation studies shows clinical and cytogenetic variability in CdCS. High resolution G banding karyotyping with chromosomal microarray analysis (CMA) is the definitive method for a precise diagnosis of CdCS. There is no specific therapy for CdCS but early rehabilitative and educational interventions improve the prognosis and is crucial for social rehabilitation. Here the authors reported this case in view of its rarity and classical clinical features and molecular cytogenetic findings.